The Epizootiology of the helminth fauna of the digestive tract of the chacma baboon Papio ursinus (Kerr, 1792) from different localities in the Transvaal - Van Hoven, Wouter (University of Pretoria, 2024)
Dissertation (MSc (Zoology))--University of Pretoria, 1982.